High Community Transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Associated With Decreased Contact Tracing Effectiveness for Identifying Persons at Elevated Risk of Infection—Vermont . (24th June 2022) - Borah, Brian F; Pringle, Julia; Flaherty, Michael; Oeltmann, John E; Moonan, Patrick K; Kelso, Patsy
Abstract: Vermont contact tracing consistently identified people at risk for coronavirus disease 2019 (COVID-19). However, the prevalence ratio (PR) of COVID-19 among contacts compared with noncontacts when viral transmission was high (PR, 13.5 [95% confidence interval CI, 13.2–13.9]) was significantly less than when transmission was low (PR, 49.3 [95% CI, 43.2–56.3]).